Performance comparison of MDORA, MDORA-OD and MDORA-WD routing protocols in VANET - Mohammed D.; Mansor M.B.; Hock G.C. (American Institute of Physics Inc., 2024)
Vehicular Ad hoc Network (VANET) is one of the new technologies and differs from other ad hoc networks because it has unique characteristics. In the VANET, it is challenging to establish routing protocols due to the frequent disconnection of the connection, the topology changes in the network structure, and the high speed of vehicles. Routing is used in the VANET to di rect vehicle-to-infrastructure (V2I) or vehicle-to-vehicle (V2V) data. VANET contributes to improving intelligent transportation systems (ITS) because it can provide traffic information and increase road safety to reduce daily road accidents. This paper will focus on the position-based routing protocol, and a performance comparison will be made between the MDORA, MDORA-OD, and MDORA-WD protocols in terms of end-to-end (E2E) delay, packet delivery ratio (PDR), and communication overhead. The network was simulated in an urban environment by MATLAB. The comparison results showed that the MDORA-WD had better results than MDORA and MDORA-OD. 2023 Author(s).